Dietary fatty acid composition and the homeostatic regulation of mitochondrial phospholipid classes in red muscle of rainbow trout (Oncorhynchus mykiss). Issue 1 (21st November 2014) - Martin, Nicolas; Kraffe, Edouard; Le Grand, Fabienne; Marty, Yanic; Bureau, Dominique P.; Guderley, Helga
ABSTRACT Although dietary lipid quality markedly affects fatty acid (FA) composition of mitochondrial membranes from rainbow trout red muscle (Oncorhynchus mykiss), mitochondrial processes are relatively unchanged. As certain classes of phospholipids interact more intimately with membrane proteins than others, we examined whether specific phospholipid classes from these muscle mitochondria were more affected by dietary FA composition than others. To test this hypothesis, we fed trout with two diets differing only in their FA composition: Diet 1 had higher levels of 18:1n‐9 and 18:2n‐6 than Diet 2, while 22:6n‐3 and 22:5n‐6 were virtually absent from Diet 1 and high in Diet 2. After 5 months, trout fed Diet 2 had higher proportions of phosphatidylcholine (PC) and less phosphatidylethanolamine (PE) in mitochondrial membranes than those fed Diet 1. The FA composition of PC, PE and cardiolipin (CL) showed clear evidence of regulated incorporation of dietary FA. For trout fed Diet 2, 22:6n‐3 was the most abundant FA in PC, PE and CL. The n‐6 FA were consistently higher in all phospholipid classes of trout fed Diet 1, with shorter n‐6 FA being favoured in CL than in PC and PE. Despite these marked changes in individual FA levels with diet, general characteristics such as total polyunsaturated FA, total monounsaturated FA and total saturated FA were conserved in PE and CL, confirming differential regulation of the FA composition of PC, PE and CL. The regulated changes of phospholipid classes presumably maintain critical membrane characteristics despite varying nutritional quality. We postulate that these changes aim to protect mitochondrial function. J. Exp. Zool. 323A: 60–71, 2015. © 2014 Wiley Periodicals, Inc.